Contemporary Islamic Socialism: Conceptual Debate and Practical Implementation - Soetomo, Greg (Islamic Thought Review, 2023)
Socialism and Islam, or Islamic socialism, are two streams of thought that have continued to develop in Middle Eastern and North African societies for centuries. These two streams frequently reinforce each other. This article examines the debate and practical implementation of Islamic socialism in the thought of contemporary Muslim philosophers such as Jamal al-Dīn al-Afghanī, Salamah Mūsa, Muṣṭafa al-Sibaʽī, and ‘Ali Sharī‘atī. This study used a comparative approach by exploring primary sources from contemporary Muslim thinkers who are the subject of the study. The findings showed that socialist Islamic thinkers have creative and original thought patterns. They intensively and comprehensively explored Islamic teachings and traditions to explain and build a complete ‘Islamic Socialism’, not just a patchwork between ‘Socialism’ and ‘Islam’. In addition, some intellectuals from the modern Muslim world created theoretical ideas and showed how Islamic socialism was implemented and realized in the form of institutions.